2011
DOI: 10.1136/thx.2010.145995
|View full text |Cite
|
Sign up to set email alerts
|

CT-quantified emphysema in male heavy smokers: association with lung function decline

Abstract: Background Emphysema and small airway disease both contribute to chronic obstructive pulmonary disease (COPD), a disease characterised by accelerated decline in lung function. The association between the extent of emphysema in male current and former smokers and lung function decline was investigated. Methods Current and former heavy smokers participating in a lung cancer screening trial were recruited to the study and all underwent CT. Spirometry was performed at baseline and at 3-year follow-up. The 15th per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 31 publications
6
61
0
2
Order By: Relevance
“…Recently, Nishimura et al [12] reported the results of a multicenter observational study examining the serial change in lung function in a cohort of 279 patients with COPD, in which emphysema severity was independently associated with a rapid annual decline [12]. The association between the baseline radiologic burden of emphysema and the subsequent decline in lung function is consistent with other recent data published by both Vestbo et al [13] and Mohamed Hoesein et al [14]. Until now, no clinical parameter has been suggested as a predictor of rapid lung function decline other than current smoking and emphysema severity in COPD.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recently, Nishimura et al [12] reported the results of a multicenter observational study examining the serial change in lung function in a cohort of 279 patients with COPD, in which emphysema severity was independently associated with a rapid annual decline [12]. The association between the baseline radiologic burden of emphysema and the subsequent decline in lung function is consistent with other recent data published by both Vestbo et al [13] and Mohamed Hoesein et al [14]. Until now, no clinical parameter has been suggested as a predictor of rapid lung function decline other than current smoking and emphysema severity in COPD.…”
Section: Introductionsupporting
confidence: 80%
“…Thus, investigation of clinical factors associated with rapid lung function decline is important in assessing and treating patients with COPD. Until now, emphysema severity measured by CT has been the only clinical parameter validated as a predictor of rapid lung function decline in COPD [12,13,14]. The most recent report from the Hokkaido COPD Cohort study found that emphysema severity was independently associated with a rapid annual decline in FEV 1 in COPD [12].…”
Section: Discussionmentioning
confidence: 99%
“…Using data from 2085 current and former heavy smokers who enrolled in the Dutch–Belgian Lung Cancer Screening Trial (NELSON), Mohamed Hoesein and colleagues showed that individuals with the largest burden of CT-based ‘emphysema’ experienced the fastest decline in lung function over 3 years of follow-up. This effect was independent of age, smoking status or baseline lung function of these individuals 8. These data are in keeping with those of Yuan et al who showed that lung ‘overinflation’ was associated with a rapid decline in FEV 1 .…”
supporting
confidence: 90%
“…The clinical relevance of this observation, however, was unknown. The study by Mohamed Hoesein et al 8 offers an answer to this clinical conundrum. Using data from 2085 current and former heavy smokers who enrolled in the Dutch–Belgian Lung Cancer Screening Trial (NELSON), Mohamed Hoesein and colleagues showed that individuals with the largest burden of CT-based ‘emphysema’ experienced the fastest decline in lung function over 3 years of follow-up.…”
mentioning
confidence: 99%
“…Hoesein et al 56 reported data from a European lung cancer screening study confirming that CT evidence of emphysema was associated with poorer lung function but also, importantly, that early emphysema in the absence of impairment was a predictor of subsequent decline.…”
Section: Mechanisms and Outcome Measuresmentioning
confidence: 96%